2014
DOI: 10.1016/j.jpainsymman.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Psychiatric Involvement on Palliative Care Consult Services: Results of a National Survey

Abstract: There are shared objectives between psychiatry and palliative care; however, currently, co-involvement on treatment teams is quite limited. Future research is needed to identify ways to facilitate the interface of palliative care and psychiatry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 10 publications
2
41
0
1
Order By: Relevance
“…The issues identified in our survey are not unique to the UK or the hospice setting. Patterson et al’s 2014 survey of American hospital-based palliative care consult services demonstrated that most respondents (71%) would like psychiatry to be more involved with the palliative care service than they currently are, and the barriers identified were similar to our study [ 48 ]. However, the American survey found that 72% of consult services had some involvement with a psychiatrist, suggesting better engagement between psychiatry and palliative care than in the UK, where only 56% of the hospital-based palliative care physicians in our survey had direct access to psychiatry.…”
Section: Discussionsupporting
confidence: 80%
“…The issues identified in our survey are not unique to the UK or the hospice setting. Patterson et al’s 2014 survey of American hospital-based palliative care consult services demonstrated that most respondents (71%) would like psychiatry to be more involved with the palliative care service than they currently are, and the barriers identified were similar to our study [ 48 ]. However, the American survey found that 72% of consult services had some involvement with a psychiatrist, suggesting better engagement between psychiatry and palliative care than in the UK, where only 56% of the hospital-based palliative care physicians in our survey had direct access to psychiatry.…”
Section: Discussionsupporting
confidence: 80%
“…One study found that 97% (N=95) of residents surveyed agreed that they desired formalized palliative care training (13). Mutually, palliative care teams have expressed interest in having psychiatrists more involved, as only 10% of palliative care teams have a full-or part-time psychiatrist employed as a member on their team (14). As the interest in incorporating palliative care into end-of-life planning expands, there is potential for psychiatry to also expand into this growing field of medicine.…”
Section: Working As a Multidisciplinary Teammentioning
confidence: 99%
“…3 However, palliative care for patients with SMI (see box 1 for an overview of the care structure for patients with SMI in the Netherlands) and physical health issues is still not widely implemented, and research on this topic for this patient group is scarce. [4][5][6][7][8][9][10][11] As the interplay between physical and psychiatric symptoms of patients with SMI and physical health issues makes them particularly vulnerable and complicates healthcare provision, 7 12-15 such research would be extremely relevant.…”
Section: Introductionmentioning
confidence: 99%